2013
DOI: 10.1080/19440049.2013.810346
|View full text |Cite
|
Sign up to set email alerts
|

Selective androgen receptor modulators:in vitroandin vivometabolism and analysis

Abstract: For future targeted screening in National Residue Control Programmes, the metabolism of seven SARMs, from the arylpropionamide and the quinolinone classes, was studied in vitro using S9 bovine liver enzymes. Metabolites were detected and identified with ultra-performance liquid chromatography (UPLC) coupled to time-of-flight mass spectrometry (ToF-MS) and triple quadrupole mass spectrometry (QqQ-MS). Several metabolites were identified and results were compared with literature data on metabolism using a human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
45
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 12 publications
6
45
0
Order By: Relevance
“…Patterns of fragmentation and fragments identification have already been proposed by Thevis et al [31] and De Rijke et al [15] for andarine and enobosarm. They have therefore been considered as a basis to explain observed fragmentation using MS/MS, IM-MS/MS or IM-MS E (Figure 3).…”
Section: Q-twim-tof Ms/ms: Fragmentation Patternsmentioning
confidence: 77%
See 1 more Smart Citation
“…Patterns of fragmentation and fragments identification have already been proposed by Thevis et al [31] and De Rijke et al [15] for andarine and enobosarm. They have therefore been considered as a basis to explain observed fragmentation using MS/MS, IM-MS/MS or IM-MS E (Figure 3).…”
Section: Q-twim-tof Ms/ms: Fragmentation Patternsmentioning
confidence: 77%
“…One animal was orally administered a unique dose of enobosarm (GTx-024, GTx Inc., Memphis, TN, USA) (200 mg) in ethanolic solution diluted in apple juice, adapted from a protocol described by De Rijke et al [15] The five others formed the control group and were orally administrated the same ethanol/apple juice mix without enobosarm. All were aged three months (56 ± 5 days) (solid feed and hay) and weighed approximately 100 ± 5 kg at the beginning of the experiment.…”
Section: Animal Experimentsmentioning
confidence: 99%
“…[15][16][17] SARMs may also exhibit a high potential for misuse in animal husbandry as growth promoters to increase weight gain, improve carcass quality, and reduce production costs. More studies are necessary to develop the comprehensiveness of SARMs metabolism through in vivo approaches, [20,21] as already available for humans and horses. Efficient analytical strategies to detect the use of SARMs have already been proposed and while main developments have been realized in the human anti-doping arena, few applications are now available in food producing animals.…”
Section: Introductionmentioning
confidence: 99%
“…[18,19] Since these compounds have recently emerged, they have not been investigated a lot. [21] Bicalutamide exhibits an anti-androgen effect and is used for the treatment of human non-metastatic prostate cancer. We therefore propose in this study to investigate further SARMs elimination and metabolism in bovine.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Furthermore, the identification of metabolites also corroborates that a substance has passed through a metabolic system and that an adverse finding is not caused by contamination of the sample. The metabolism of different SARMs of the arylpropionamide class has been studied in vitro in a variety of systems such as human liver microsomes, [8] equine liver microsomes, [9] bovine liver microsomes [10] and fungal incubates, [11] as well as in vivo in both human [12,13] and equine [14] urine. The three aforementioned in vivo studies showed that the SARMs were metabolized rapidly and extensively.…”
mentioning
confidence: 99%